Goal-relevant situations facilitate memory of neutral faces. - Montagrin, Alison; Sterpenich, Virginie; Brosch, Tobias; Grandjean, Didier; Armony, Jorge; Ceravolo, Leonardo; Sander, David (Cognitive, Affective & Behavioral Neuroscience, 2018)
Emotional situations are typically better remembered than neutral situations, but the psychological conditions and brain mechanisms underlying this effect remain debated. Stimulus valence and affective arousal have been suggested to explain the major role of emotional stimuli in memory facilitation. However, neither valence nor arousal are sufficient affective dimensions to explain the effect of memory facilitation. Several studies showed that negative and positive details are better remembered than neutral details. However, other studies showed that neutral information encoded and coupled with arousal did not result in a memory advantage compared with neutral information not coupled with arousal. Therefore, we suggest that the fundamental affective dimension responsible for memory facilitation is goal relevance. To test this hypothesis at behavioral and neural levels, we conducted a functional magnetic resonance imaging study and used neutral faces embedded in goal-relevant or goal-irrelevant daily life situations. At the behavioral level, we found that neutral faces encountered in goal-relevant situations were better remembered than those encountered in goal-irrelevant situations. To explain this effect, we studied neural activations involved in goal-relevant processing at encoding and in subsequent neutral face recognition. At encoding, activation of emotional brain regions (anterior cingulate, ventral striatum, ventral tegmental area, and substantia nigra) was greater for processing of goal-relevant situations than for processing of goal-irrelevant situations. At the recognition phase, despite the presentation of neutral faces, brain activation involved in social processing (superior temporal sulcus) to successfully remember identities was greater for previously encountered faces in goal-relevant than in goal-irrelevant situations.